2016
DOI: 10.1099/ijsem.0.000746
|View full text |Cite
|
Sign up to set email alerts
|

Actinoplanes lichenis sp. nov., isolated from lichen

Abstract: A novel species of the genus Actinoplanes, strain LDG1-22 T , for which we propose the name Actinoplanes lichenis sp. nov., was isolated from a lichen sample collected from tree bark in Thailand. The taxonomic position of the species has been described based on a polyphasic approach. Strain LDG1-22 T produced irregular sporangia on agar media. It contained mesodiaminopimelic acid in the cell-wall peptidoglycan. The major menaquinone was MK-9(H 4 ); the polar lipids were diphosphatidylglycerol, phosphatidyletha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…At the time of writing, the genus Actinoplanes comprises 47 validly published species. Based on previous reports, we found that Actinoplanes is found in lichen habitats [5]. This study reports the taxonomic study of the two new species of Actinoplanes, represented by strains LDG1-01 T and LDG1-06 T .…”
supporting
confidence: 56%
“…At the time of writing, the genus Actinoplanes comprises 47 validly published species. Based on previous reports, we found that Actinoplanes is found in lichen habitats [5]. This study reports the taxonomic study of the two new species of Actinoplanes, represented by strains LDG1-01 T and LDG1-06 T .…”
supporting
confidence: 56%
“…The sporangia were 4.6-8.7 μm in size (Fig. S1) with irregular shape similar to Actinoplanes nipponensis (Wink et al 2014), Actinoplanes lichenis (Phongsopitanun et al 2016) and Actinoplanes luteus (Suriyachadkun et al 2015). The sporangiospores were motile.…”
Section: Phenotypic Characteristicsmentioning
confidence: 97%
“…2). The results of genome analysis indicated that NEAU-J3 T contained a total of 8534 genes, of which 7458 genes were annotated and l-Lys, l-lysine; Ara, arabinose; Gal, galactose; Glc, glucose; Xyl, xylose; Man, mannose; Rib, ribose *Data from Jia et al [6]; †Data from Han et al [27]; ‡Data from Phongsopitanun et al [28]; §Data from Tamura et al [29]; ¶Data from Ara et al [30]; #Data from Ara and Takuji [31]. Table 1.…”
Section: Genomic Characterizationmentioning
confidence: 99%
“…[27]; ‡Data from Phongsopitanun et al . [28]; §Data from Tamura et al . [29]; ¶Data from Ara et al .…”
Section: Average Nucleotide Identity and Dna–dna Hybridizationmentioning
confidence: 99%